ASPIRASI MASYARAKAT DAERAH SEBAGAI PROGRAM PRIORITAS PEMBANGUNAN DAERAH YANG DIJAMIN KONSTITUSI - Gokma Toni Parlindungan S (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Aspirations of the people is one key to success for central or regional development. Regional Representative Council as a representative of the people of the region must take the time to listen to the aspirations of local communities. This study will discuss the role of the Regional Legislative Assembly of representatives in the community aspirations as guaranteed by the Constitution. This research method is sociological normative. So this research, is expected to explain the mechanism that is responsive in the aspiration of society by the local council, knowing the role of the Regional Representative Council in voicing the aspirations of the people in the priority programs of regional development. Aspirations of the people is the voice of the people to be delivered in the formation of legislation. So that created regional development priorities is responsive to the community and the region.